Elucidating pathogenic determinants in stenotrophomonas maltophilia pathogenesis - Thomas, Renjan (2014)
Stenotrophomonas maltophilia, Gram negative bacteria has been known to be an environmental microbe with numerous biotechnological applications. They are ubiquitously found in nature. In recent times, this bacterium has been documented to be one of the leading nosocomial pathogen next to Pseudomonas aeruginosa. Owing to the high incident rate in hospital setup, they have been ranked as an opportunistic pathogen and have been associated with bacteremic infection and pneumonia, both with high rate of mortality in immunocompromised patients. Mortality rate has been found to be high with patients who have a history of prolonged hospitalization,malignancy, neutropenia, immune suppression, breakdown of mucocutaneous defence barriers (e.g., following catheterization, artificial implantation, tracheotomy,or peritoneal dialysis), exposure to broad spectrum antibiotics and those requiring mechanical ventilation. Their intrinsic/acquired resistance to most antibiotics and their ability to colonize surfaces of medical devices makes S. maltophilia a potentially dangerous pathogen. Treatment of S. maltophilia infections is also complicated by the fact that isolates are inherently resistant to many of the currently available broad-spectrum agent including carbapenems. Whether S. maltophilia clinical isolates are colonizers or true pathogens is still controversial. Despite the increase in the spectrum of clinical syndromes associated with S. maltophilia, very little is known about the extracellular enzymes profiles which may have potential roles in pathogenesis especially among clinical isolates associated with infections. In this study, we screened and compared an array of extracellular enzymes in S.maltophilia collected from invasive and non-invasive clinical specimens by substrate plate assays. We also grouped the isolates as device related and non-device related and compared the enzyme profile. Our study showed all clinical isolates produced substantial levels of biochemical enzyme assayed. However, lecithinase and heparinase were significantly associated with isolates of invasive origin. In contrast, device related and non-device related did not show an major significant difference. These data suggest that clinical isolates of S. maltophila are a reservoir for pathogenic potential enzymes. The pathogenic potential of S. maltophilia strains isolated from clinical samples were screened for a panel of putative virulent genes such asputative lipase, putative iron complex outer membrane [ICOM], putative siderophore, lux R, toxA, piliZ and tatD which were fished out from closely related P. aeruginosa genome. The results showed that among the 108 isolates, 57.4%, 10.1%, 0.92%, 57.4% and 74% of the isolates harboured ICOM (n = 62), siderophore (n = 11), luxR (n = 1), Lipase (n =62) and tatD (n = 80) harboured these genes. ToxA and piliz were not found in these clinical isolates. Relative quantification of these putative virulent genes showed ICOM, tatD and lipase genes to be overexpressed compared to others. Environmental strain S. maltophilia LMG 959 lacked these putative virulent genes. The role of S. maltophilia on macrophages was studied to determine the inflammatory response and to study the phagocytic ability of this bacterium on RAW 264.7 macrophages. Both invasive and non-invasive isolates of S. maltophilia were able to enter the macrophage cells. Greater internalization ability was observed by clinical isolates ofS.maltophilia in comparison to that of the environmental strain. S. maltophilia LMG959 (p < 0.05). Although all isolates of S. maltophilia gained entry, only the clinical isolates were able to replicate within the macrophages. Environmental strain was unable to replicate within the macrophage. The ability of clinical isolates of S. maltophilia to enter and survive the macrophages indicates its resistance to host defence system. Clinical isolates of S. maltophilia induced an amplified level of activation within macrophages which triggered immune response compared to environmental strains, as revealed by increased nitric oxide production and CD40 expression. Intracellular survivability of S. maltophilia was also ascertained by the presence of several bacteria which were observed as membrane bound. This intracellular phase during infection could play a prominent role in immune evasion and its pathogenicity. In conclusion, S. maltophilia has all the essential qualities to be termed as a serious nosocomial pathogen with the presence of these virulence factors such as the extracellular enzymes and the gene products which could have a deleterious effect owing to the fact that the virulent determinants act in combination. Evading host defences and having intracellular survival ability makes this bacterium a potent and serious nosocomial pathogen.